Cognitive authorities of COVID-19 information: educational differences and outcomes of trust in health experts and social media influencers in Finland - Sanna Malinen; Aki Koivula (Information Research: An International Electronic Journal)
Introduction. This study investigates people’s trust in institutional healthcare experts and social media influencers as sources of COVID-19 information. Using the notion of ‘cognitive authority’, this study examines trusted information sources during the pandemic, how the education level explains this trust, and how trusted COVID-19 information sources are associated with people’s attitudes towards vaccines.